Impact of sleeve gastrectomy and dietary change on metabolic and hepatic function in an obesity rat model - Experimental research. (March 2020) - Dohmen, Jonas; Praktiknjo, Michael; Rudeloff, Anna; Uschner, Frank Erhard; Klein, Sabine; Plamper, Andreas; Matthaei, Hanno; Rheinwalt, Karl-Peter; Wehner, Sven; Kalff, Jörg C.; Trebicka, Jonel; Lingohr, Philipp
Abstract: Purpose: Sleeve gastrectomy (SG) is an effective procedure to treat morbid obesity. SG induces remission of type 2 diabetes and metabolic syndrome and improves non-alcoholic fatty liver disease (NAFLD). However, it is imperative to clarify the extent to which these beneficial effects may be attributed to SG among other concomitant changes including postoperative diet. The current study addresses this question in a rodent model of obesity by subjecting it to SG, normal diet, or a combination of the two. Methods: Male Wistar-rats were fed with either high fat diet (HF, n = 32) or received chow diet (CD, n = 8). After 15 weeks, the HF-fed rats underwent either SG or sham operation, following which they were randomised to either continue HF or switched to CD for another 6 weeks. Body weight, fasting blood glucose level, blood pressure, and adipokine expression (leptin, adiponectin, MCP-1) in the adipose tissue along with triglycerides level in the blood serum were assessed to evaluate metabolic function. Hepatic function was assessed by histological evaluation of liver fibrosis (Hydroxyproline, Sirius Red) and reverse transcription polymerase chain reaction (RT-PCR) of the inflammation marker monocyte chemoattractant protein-1 (MCP-1). Results: Postoperative dietary change improved adipose tissue inflammation and arterial blood pressure regardless of the surgical intervention, while SG improved hyperglycaemia, blood triglyceride levels and, regardless of the postoperative diet, hepatic inflammation and fibrosis. However, combined administration of SG with post-operative normal diet was the most effective with regard to reducing the body weight. Conclusion: HF for 15 weeks induced obesity with metabolic syndrome and NAFLD in rats. SG and dietary intervention improved metabolic state and NAFLD; however, their combination was significantly more effective. Highlights: Sleeve gastrectomy and subsequent diet change improved hepatic function and NAFLD. The impact of diet change on weight loss is more distinct than sleeve gastrectomy. Regardless of the diet, sleeve gastrectomy improves liver inflammation and fibrosis.